Ciri-Ciri Fiziko-Kimia Tanih di Lembangan Sg. Bernam- Guna Tanah Pertanian - Saad Azlina, Othman Zainudin, Yusof Norjan (N/A, 2012)
Ciri-Ciri Fiziko-Kimia Tanih di Lembangan Sg. Bernam- Guna Tanah Pertanian by Saad Azlina, Othman Zainudin, Yusof Norjan,